Exploring Roman picture lamp breakage rituals in light of mechanical experimentation. Issue 2 (December 2022) - Lapp, Eric C.
Abstract: Intentionally broken "picture" lamps, or Bildlampen, are relatively common at archaeological sites throughout the Roman world. Such lamps typically exhibit a missing central discus. The discus itself – called a lamp "medallion" – often survives, too, and represents further evidence for deliberate lamp breakage. This article explores picture lamps with missing discuses and lamp medallions as a distinct and identifiable artifact group. It also surveys the possible reasons behind their intentional breaking. The work additionally identifies selected findspots where the lighting vessels were broken in rituals, with a special focus on the Shrine of Apollo at Tyre, and examines whether lamp breakage reflects individual choice or collective behavior. In an effort to understand how Roman picture lamps were deliberately broken and the lamp medallions generated for rituals, breakage experiments – drop, impact, puncture, and hammerstone – were conducted on accurate museum-made replicas of Roman picture lamps.